Videoaulas de matemática voltadas ao desenvolvimento de esquemas cognitivos - Machado, Pedro André Pires (2024)
This doctoral research presents an exploratory mixed-methods study that investigated the impact of access to short math video lessons, designed based on Conceptual Fields Theory and Cognitive Load Theory, on the development of cognitive schemas among high school students. The research proposal is divided into three phases: 1) selection of situations; 2) development and application of video lessons and data collection instruments; and 3) data analysis and interpretation. In the first phase, a content analysis was conducted on the statements of 1,305 math questions from the ENEM exams, spanning from 2009 to 2021, to map how these questions embed the Conceptual Field of Geometry in context. In the second phase, based on the selected situations, three playlists of video lessons were created, each accompanied by questionnaires with open and closed questions. These materials were applied to one hundred high school students from a school in Rio Grande do Sul and covered topics such as unit conversion, scale, and the application of the Pythagorean theorem in various two- and threedimensional contexts. In the third phase, quantitative and qualitative data were analyzed and interpreted using the Randomized Complete Block Design and Content Analysis. After separate analyses, the datasets were integrated to identify convergences, divergences, and correlations, allowing for a broader and deeper understanding of the findings. A final activity was also conducted, involving the creation of math video lessons by the study participants.The research findings indicate that the video lessons supported the development and refinement of geometric schemas among students, in alignment with their knowledge. However, an investigation into the duration of the video lessons revealed that increased topic complexity reduces the positive impact of short-duration materials. Furthermore, qualitative data analysis showed that many students value the effort teachers put into creating their own video lessons and tend to use them as needed for learning the curriculum content. In addition to fostering mathematical knowledge and audiovisual production skills, the activity of creating video lessons also reinforced collaborative skills and strengthened bonds among peers.